1996
DOI: 10.1128/jvi.70.7.4246-4252.1996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of inhibition of M2 ion channel activity by BL-1743, an inhibitor of influenza A virus

Abstract: The influenza A virus M 2 integral membrane protein has ion channel activity that can be inhibited by theantiviral drug amantadine. Recently, a spirene-containing compound, BL-1743 {2-[3-azaspiro (5,5)undecanol]-2-imidazoline}, that inhibits influenza virus growth was identified (S. Kurtz, G. Luo, K. M. Hahnenberger, C. Brooks, O. Gecha, K. Ingalls, K.-I. Numata, and M. Krystal, Antimicrob. Agents Chemother. 39:2204-2209, 1995). We have examined the ability of BL-1743 to inhibit the M 2 ion channel when expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…Two promising new drugs, 4guanidino-Neu5Ac2en (4-GuDANA) and GS4104, were designed to inhibit the viral enzyme neuraminidase (56), and they are currently being evaluated for clinical use (31), but resistance to at least one of these neuraminidase inhibitors has already been encountered in laboratory settings (31,36). New inhibitors of the ion channel activity of the viral M2 protein (43) and of the viral polymerase (42) have only recently been identified. Drugs that inhibit HA-mediated membrane fusion would thus be a welcome addition to the anti-influenza virus armamentarium.…”
Section: Discussionmentioning
confidence: 99%
“…Two promising new drugs, 4guanidino-Neu5Ac2en (4-GuDANA) and GS4104, were designed to inhibit the viral enzyme neuraminidase (56), and they are currently being evaluated for clinical use (31), but resistance to at least one of these neuraminidase inhibitors has already been encountered in laboratory settings (31,36). New inhibitors of the ion channel activity of the viral M2 protein (43) and of the viral polymerase (42) have only recently been identified. Drugs that inhibit HA-mediated membrane fusion would thus be a welcome addition to the anti-influenza virus armamentarium.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of M2 was initially reported by (Lamb et al, 1985Lai, 1981) Pinto et al (1992) then demonstrated its ion channel activity in Xenopus laevis oocytes injected with M2 RNA and measured by the two-electrode voltage clamp (TEVC) method of electrophysiology, which has become the most common assay by far to measure M2 conductance and its inhibition by small molecules. However, several groups have used a variety of electrophysiological techniques including whole-cell patch-clamp of mammalian cells to probe the ion conduction properties of M2 (Chizhmakov et al, 1996;Holsinger et al, 1995Holsinger et al, , 1994Jalily et al, 2016;Shimbo et al, 1996;Tu et al, 1996;Wang et al, 1995Wang et al, , 1993 For example, Chizhmakov et al (1996) expressed M2 in mouse erythroleukemia cells and also observed selective conduction of protons.…”
Section: Regulation Of Ion Conduction By M2mentioning
confidence: 99%
“…Amantadine, known as one of the first drugs against influenza A, blocks the proton channel M2 in a concentration of up to 5 mM (Chizhmakov et al, 1996;Hay et al, 1985;Tu et al, 1996) by changing M2 dynamics (Hu et al, 2007). Depending on the technique used, the drug may either enter the pore (X-ray crystallography: Stouffer et al, 2008) or diffuses into hydrophilic/hydrophobic pockets in the outer rim of the bundle (NMR spectroscopy: Schnell and Chou, 2008).…”
Section: Small Molecule Drugsmentioning
confidence: 99%